The Effectiveness of Modified Video-Based Shadowing to Improve 7th-Grade Madurese Students’ English Pronunciation - Tasyawfi, Anataya; Lolita, Yuri (Indonesian Journal Publisher, 2025)
This study investigated the effectiveness of modified video-based shadowing as a teaching technique to enhance the Madurese students’ English pronunciation. This true experimental research involved two groups of 7th-grade students. An experimental group received treatment using the video-based shadowing technique and a control group followed the traditional teaching technique. Students were given read-aloud pre- and post-tests and pronunciation exercises. They were assessed using pronunciation checker tools to ensure accurate measurements. The results revealed that the experimental group showed a significant increase in their post-test scores, from 38.68 to 43.91, while the control group exhibited a decline from 36.01 to 33.28. The common pronunciation errors made by the students were substitutions, such as pronouncing the word /let/ as /lɪt/, or /ˈbrekfəst/ as /brɪgfəs/. However, there was a noticeable reduction in the frequency of this error among the students in the experimental group. Based on the positive result, the researcher implied that this technique is suggested for teachers to improve students’ English pronunciation.